Assessment of the Myogenic Stem Cell Compartment Following Transplantation of Pax3/Pax7-Induced Embryonic Stem Cell-Derived Progenitors - Darabi, Radbod (2011)
An effective long-term cell therapy for skeletal muscle regeneration requires donor contribution to both muscle fibers and the muscle stem cell pool. Although satellite cells have these abilities, their therapeutic potential so far has been limited due to their scarcity in adult muscle. Myogenic progenitors obtained from Pax3-engineered mouse embryonic stem (ES) cells have the ability to generate myofibers and to improve the contractility of transplanted muscles in vivo, however whether these cells contribute to the muscle stem cell pool and are able to self-renew in vivo is still unknown. Here we addressed this question by investigating the ability of Pax3, which plays a critical role in embryonic muscle formation, and Pax7, which is important for maintenance of the muscle satellite cell pool, to promote the derivation of self-renewing functional myogenic progenitors from ES cells. We show that Pax7, like Pax3, can drive the expansion of an ES-derived myogenic progenitor with significant muscle regenerative potential. We further demonstrate that a fraction of transplanted cells remains mononuclear, and displays key features of skeletal muscle stem cells, including satellite cell localization, response to re-injury and contribution to muscle regeneration in secondary transplantation assays. The ability to engraft, self-renew, and respond to injury provide foundation for the future therapeutic application of ES-derived myogenic progenitors in muscle disorders.